Mycobacterium tuberculosis MmsA (Rv0753c) Interacts with STING and Blunts the Type I Interferon Response - Yifan Sun (American Society for Microbiology, 2020)
ABSTRACT Type I interferon (IFN) plays an important role in Mycobacterium tuberculosis persistence and disease pathogenesis. M. tuberculosis has evolved a number of mechanisms to evade host immune surveillance. However, it is unclear how the type I IFN response is tightly regulated by the M. tuberculosis determinants. Stimulator of interferon genes (STING) is an essential adaptor for type I IFN production triggered by M. tuberculosis genomic DNA or cyclic dinucleotides upon infection. To investigate how the type I IFN response is regulated by M. tuberculosis determinants, immunoprecipitation-mass spectrometry-based (IP-MS) proteomic analysis was performed to screen proteins interacting with STING in the context of M. tuberculosis infection. Among the many predicted candidates interacting with STING, the M. tuberculosis coding protein Rv0753c (MmsA) was identified. We confirmed that MmsA binds and colocalizes with STING, and the N-terminal regions of MmsA (amino acids [aa] 1 to 251) and STING (aa 1 TO 190) are responsible for MmsA-STING interaction. Type I IFN production was impaired with exogenous expression of MmsA in RAW264.7 cells. MmsA inhibited the STING-TBK1-IRF3 pathway, as evidenced by reduced STING levelS and subsequent IRF3 activation. Furthermore, MmsA facilitated p62-mediated STING autophagic degradation by binding p62 with its C terminus (aa 252 to 455), which may account for the negative regulation of M. tuberculosis MmsA in STING-mediated type I IFN production. Additionally, the M. tuberculosis mmsA R138W mutation, detected in a hypervirulent clinical isolate, enhanced the degradation of STING, implying the important relevance of MmsA in disease outcome. Together, we report a novel mechanism where M. tuberculosis MmsA serves as an antagonist of type I IFN response by targeting STING with p62-mediated autophagic degradation. IMPORTANCE It is unclear how the type I IFN response is regulated by mycobacterial determinants. Here, we characterized the previously unreported role of M. tuberculosis MmsA in immunological regulation of type I IFN response by targeting the central adaptor STING in the DNA sensing pathway. We identified STING-interacting MmsA by coimmunoprecipitation-mass spectrometry-based (IP-MS) proteomic analysis and showed MmsA interacting with STING and autophagy receptor p62 via its N terminus and C terminus, respectively. We also showed that MmsA downregulated type I IFN by promoting p62-mediated STING degradation. Moreover, the MmsA mutant R138W is potentially associated with the virulence of M. tuberculosis clinical strains owing to the modulation of STING protein. Our results provide novel insights into the regulatory mechanism of type I IFN response manipulated by mycobacterial MmsA and the additional cross talk between autophagy and STING in M. tuberculosis infection, wherein a protein from microbial pathogens induces autophagic degradation of host innate immune molecules.